Efficacy of elongated needles for motor and balance function after a stroke: a systematic review and meta-analysis - Zhang, Shuyan; Zhou, Haichun (Frontiers in Neurology, 2025)
IntroductionThis systematic review aimed to evaluate the efficacy and safety of elongated needle therapy in improving motor and balance functions after stroke, to inform its clinical adoption in rehabilitation.Methods and AnalysisWe searched PubMed, Web of Science, EMBASE, Medicine, CNKI, CBM, Wanfang, and VIP from inception to May 1, 2024, for randomized controlled trials (RCTs) assessing elongated needles for post-stroke limb movement and balance dysfunction. Primary outcomes were balance and motor ability; secondary outcomes included Activities of Daily Living (ADL) and adverse events. Meta-analysis used RevMan 5.4 and Stata 16.0. Heterogeneity was explored via subgroup/meta-regression/sensitivity analyses (if significant). Two reviewers independently assessed bias risk using Cochrane tools. Outcome quality was evaluated with GRADE.ResultsThis meta-analysis included 18 randomized controlled trials (RCTs), encompassing a total of 1,230 subjects. The results indicated that elongated needles, utilized either as a solo intervention or in conjunction with other modalities, markedly enhanced balance capabilities in stroke patients when compared to conventional acupuncture, rehabilitation training, oral Chinese medicine, and alternative therapies including electroacupuncture and acupoint sticking (MD = 6.34, P < 0.001, I2 = 85%, 95% CI = 4.80–7.89). Furthermore, elongated needles, whether applied alone or in combination with other therapies, significantly improved the motor function of limbs in patients (SMD = 1.21, P < 0.00001, I2 = 92%, 95% CI = 0.63–1.79). Additionally, elongated needles, when used alone or in conjunction with other treatments, demonstrated greater efficacy in enhancing patients' activities of daily living compared to conventional acupuncture alone, rehabilitation training, or their combined regimen (SMD = 1.13, P < 0.00001, I2 = 83%, 95% CI = 0.70–1.55). However, further clinical research is warranted to substantiate the advantages of elongated needles over other therapies, including electroacupuncture and acupoint sticking. In terms of safety, the overwhelming majority of the studies included in the analysis reported the absence of adverse reactions.ConclusionEvidence from current studies indicates that elongated needle may improve post-stroke patients' balance and motor function, and enhance their daily living skills. However, the number of rigorous scientific studies is limited, and there is considerable variability across studies, limiting the confidence in these findings. Therefore, the clinical effectiveness of this treatment still requires additional validation. It is imperative to conduct more high-quality, large-scale, multi-center RCTs that conform to international guidelines to establish the efficacy of this therapy's clinical applications.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024542151.